Co-existing bipolar disease and 17q12 deletion: a rare case report. (February 2022) - Bulu, Ersel; Kalayci Yigin, Aysel; Agirbasli, Deniz; Demirel, Omer Faruk; Aksoy Poyraz, Cana; Seven, Mehmet
Abstract : Background: 17q12 microdeletion syndrome is a rare autosomal dominant chromosomal anomaly, caused by the deletion of a 1.4 Mb–spanning DNA sequence on the long arm of chromosome 17. Herein, we report the first bipolar disease (BPD) case with a 1.6-Mb deletion in the 17q11.2-17q12 chromosome region. Materials and methods: Physical examination of the case was performed. Karyotype and microarray analyses were performed for the case and the parents. Results: Physical examination revealed mild dysmorphic features such as high and forehead, full cheeks, slightly depressed nasal bridge and arched eyebrow. Chromosomal analysis of the patient revealed 46, XX, del(17)(q12) karyotype, and parents' karyotype were normal. In the microarray analysis of patient, 1.6 megabases deletion was detected in the 17q12 region [arr(hg19) 17q12 (34, 611, 352–36, 248, 918) ×1]. The microarray analysis of the mother was normal. The father's microarray showed 473 kilobases duplication in the 11p11.12 region. Conclusion: Although 17q12 deletion syndrome has been associated with bipolar disorder, very few such cases have been described in the literature. Genetic counseling should be considered in patients with remarkable phenotype, complex symptomatology, neurodevelopmental disorder and additional conspicuous medical conditions.